Breast Cancer Therapies: A Review - S. Adebayo, Kehinde; J. Ajao, Jadesola; M. Oderemi, Oluwagbemisola; P. Ughagwu, Kelechukwu (Asian Pacific Journal of Cancer Biology, 2024)
Breast cancer is the most frequent cause of cancer-related deaths among postmenopausal women. It is the leading cause of cancer-related death in women worldwide. The human epidermal growth factor receptor 2 (HER2) is overexpressed in roughly 30% of all breast cancers. Breast cancers that are human epidermal growth factor receptor 2 (HER2) -positive are frequently and especially aggressive, as this receptor has been shown to promote cancer growth. Before the advent of HER2-specific monoclonal antibodies, HER2-positive breast cancers had a poor prognosis. Clinical results for HER2-positive breast cancer have, however, changed significantly since the introduction of monoclonal antibodies and antibody-drug conjugates in therapy. Monoclonal antibodies (mAb) such as trastuzumab and pertuzumab attach to the HER2 receptor protein, deactivating it or mobilizing the immune system to aid in the destruction of cells that produce it. The remarkable accomplishments in the development of HER2-targeted therapies, along with a better understanding of the disease’s biology, have improved clinical outcomes over the years. Resistance however still poses a significant challenge, emphasizing the vital need of developing novel agents. This review article examines the mechanisms underlying the action of these therapies with an overview of their advancements and setbacks in breast cancer treatment in the last decade.